Exploring the Forms and Functions of Film, Comic Book, and Video Game Narration: A Transmedial Approach to Narratology and Contemporary Media Culture (KULT_online, 2017)
Jan-Noël Thon's transmedial approach in Transmedial Narratology and Contemporary Media Culture (2016) provides a synergistic analysis of how narration in films, comic books, and video games works. Focusing on the three aspects of storyworld, narrator, and subjectivity, it sheds light on the forms and functions of these elements and their representations in contemporary texts. It thus also facilitates the comparison and transmedial application of many narratological theories.